STREPTOCOCCAL GINGIVOESTOMATITIS IN TIME OF COVID-19 - Llerena-Noda, Viviana Yanin (2021)
Considering other pathogens in febrile syndromes during the COVID-19 pandemic is a necessity in primary health care and reverts to greater relevance in the examination of the oral cavity. With the objective of describing a case of a young patient with suspected COVID-19, who is diagnosed with streptococcal gingivostomatitis, this article is carried out. Reference is made to the symptoms and signs shared by both entities and to the reports of research studies that attribute new clinical manifestations in the oral cavity to the SARS-CoV-2 virus.